2011
DOI: 10.1002/bmc.1663
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of paraquat in postmortem samples by gas chromatography–ion trap mass spectrometry and review of the literature

Abstract: Paraquat (PQ) is an herbicide implicated in numerous fatalities, mainly caused by voluntary ingestion. Several methods have been used to quantify PQ in plasma and urine samples of intoxicated humans as a predictor of clinical outcome. There is no validated method for the analysis of PQ in postmortem samples. Therefore, the aim of this study was to develop an analytical method, using gas chromatography-ion trap mass spectrometry (GC-IT/MS) after solid-phase extraction, to quantify PQ in postmortem samples, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Analytical method validation is a mandatory step to evaluate the ability of developed methods to provide accurate results for their routine application. The validation of the method was performed according to European Medicines Agency () and other studies (Gouveia et al ., ; Moreira et al ., ). The European Medicines Agency guidelines relies on the US Food and Drug Administration guidance (US Department of Health and Human Services et al ., ), which is now almost generally accepted by the biopharmaceutical industries as the gold standard method validation approach (Smith, ).…”
Section: Methodsmentioning
confidence: 97%
“…Analytical method validation is a mandatory step to evaluate the ability of developed methods to provide accurate results for their routine application. The validation of the method was performed according to European Medicines Agency () and other studies (Gouveia et al ., ; Moreira et al ., ). The European Medicines Agency guidelines relies on the US Food and Drug Administration guidance (US Department of Health and Human Services et al ., ), which is now almost generally accepted by the biopharmaceutical industries as the gold standard method validation approach (Smith, ).…”
Section: Methodsmentioning
confidence: 97%
“…The carrier gas was helium C‐60 at a constant flow‐rate of 1 ml min –1 . All conditions were set as described previously (Moreira et al ., ). Results are presented in nmol PQ per mg of protein.…”
Section: Methodsmentioning
confidence: 97%
“…To date, various studies about PQ poisoning have been conducted. Some studies have evaluated the detection and toxicokinetics of PQ in humans, [4][5][6][7][8] while others have evaluated the effects of the treatment such as early hemoperfusion in PQ poisoned patients. [9][10][11] The study on toxic mechanism revealed that PQ is concentrated inside the cells of multiple organs where it undergoes redox cycling.…”
mentioning
confidence: 99%